2022
DOI: 10.3233/bmr-191826
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a home physical exercise program in patients with osteoporotic vertebral fractures: A retrospective observational study

Abstract: BACKGROUND: Adherence to treatment is one of the most common problems in patients suffering from chronic disease such as osteoporosis, and special commitment is required to patients, especially regarding rehabilitation. There is increasing evidence that physical interventions aimed at relieving pain and reducing physical impairments could play a crucial role in improving the quality of life and reducing the risk of fractures in patients with severe osteoporosis. OBJECTIVE: The aim of this study was to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A tailored rehabilitation program based on balance and muscle strength tests has recently been proposed as an effective treatment option for basic motor function improvement and disability reduction [ 29 , 30 ]. A retrospective observational study found that compliance with a home exercise program was 62.86%, with several causes of non-compliance, including the absence of supervision by health personnel and a lack of motivation [ 31 ]. The use of exercise is still controversial, and more research is needed to maximize its clinical relevance [ 20 ].…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…A tailored rehabilitation program based on balance and muscle strength tests has recently been proposed as an effective treatment option for basic motor function improvement and disability reduction [ 29 , 30 ]. A retrospective observational study found that compliance with a home exercise program was 62.86%, with several causes of non-compliance, including the absence of supervision by health personnel and a lack of motivation [ 31 ]. The use of exercise is still controversial, and more research is needed to maximize its clinical relevance [ 20 ].…”
Section: Conservative Treatmentmentioning
confidence: 99%